Empirical Research on Sustainability in Mitigating Fuel Emissions and Enhancing Load Performance of Internal Combustion Engines - Abdelgader A.S. Gheidan; Mazlan Bin Abdul Wahid; Opia Anthony Chukwunonso (Current Approaches in Engineering Research and Technology Vol. 3, 2024)
Internal combustion engine (ICE) is regarded as one of the famous mode of power generation and the prime mover in automotive application. As technology strives with increase in energy demand, there is need of adopting reliable techniques towards maintaining green environment without affecting production. This study aims to know fossil and biomaterial feedstock with different percentages of NOx emissions generation. This research reviews the effective ways of reducing the various pollutants (NOx, CO, HC and smoke) emissions from different fuel types (petroleum and biodiesel). This centered on some factors on high generation of NOx emissions from biofuel and fossil which include flame adiabatic temperature, molecular structure of the bio-material (biofuel) and fossil, load conditions and ignition delay time. The paper further stated the adequate methods for reduction of NOx, HC, smoke and others for both in pre and post combustion approaches. However, the observed results from the adopted technologies indicates that EGR introduced, reduced the NOx emissions at about 5-25% EGR rate when used with bio-fueled engine. This is achievable via controlling the combustion peak temperature and oxygen content, also shows significant drop in CO and HC emissions. In the technique of water injection mode, significant decrease in NOx emissions by about 50% with little increase in the content of CO product were observed in the test of biodiesel. Finally, with this techniques and modifications, the fuel emissions will be greatly minimized for better environment for operational activities.